2013
DOI: 10.1186/1556-276x-8-150
|View full text |Cite
|
Sign up to set email alerts
|

Diameter-sensitive biocompatibility of anodic TiO2 nanotubes treated with supercritical CO2 fluid

Abstract: This work reports on the diameter-sensitive biocompatibility of anodic TiO2 nanotubes with different nanotube diameters grown by a self-ordering process and subsequently treated with supercritical CO2 (ScCO2) fluid. We find that highly hydrophilic as-grown TiO2 nanotubes become hydrophobic after the ScCO2 treatment but can effectively recover their surface wettability under UV light irradiation as a result of photo-oxidation of C-H functional groups formed on the nanotube surface. It is demonstrated that human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Park et al reported that vitality, proliferation, migration, and differentiation of MSCs and hematopoietic stem cells, as well as the behavior of osteoblasts and osteoclasts were strongly affected by the nanometric scale TiO 2 surface topography with a specific response to nanotube diameters between 15 and 100 nm [12]. Our recent study also reported the diameter-sensitive cytocompatibility of TiO 2 nanotubes treated with supercritical CO 2 fluid [13]. In other words, cell vitality has an extremely close relationship with the geometric factors of TiO 2 nanotube openings.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Park et al reported that vitality, proliferation, migration, and differentiation of MSCs and hematopoietic stem cells, as well as the behavior of osteoblasts and osteoclasts were strongly affected by the nanometric scale TiO 2 surface topography with a specific response to nanotube diameters between 15 and 100 nm [12]. Our recent study also reported the diameter-sensitive cytocompatibility of TiO 2 nanotubes treated with supercritical CO 2 fluid [13]. In other words, cell vitality has an extremely close relationship with the geometric factors of TiO 2 nanotube openings.…”
Section: Introductionsupporting
confidence: 66%
“…These as-grown TiO 2 nanotubes had well-defined nanotubular structure, and their nanotube diameters were nearly proportional to the applied voltages. In addition, the XRD results from our previous study confirmed these as-grown TiO 2 nanotubes to be amorphous phase, mainly TiO 2 •xH 2 O [13]. After the Ag deposition, the surface topography of these as-grown TiO 2 nanotubes changed with the extent depending on the diameter.…”
Section: Resultsmentioning
confidence: 58%
“…8d). It has been reported that the extents of cell attachment, spreading, and cytoskeletal organization are greater on hydrophilic surfaces than on hydrophobic surfaces [44]. Based on these observations, it can be concluded that the improved wettability of the anodized specimens was due to the combination of the effects induced by both the surface oxide layer and the increased surface roughness after anodization.…”
Section: Surface Wettabilitymentioning
confidence: 89%
“…Lan et al observed an increasing trend in fibroblast cell proliferation, together with an elongated flatten morphology, on nanotubular oxides with pore diameter ranging from 15 to 50 nm compared to flat titanium; yet, a sharp drop in proliferation was exhibited by 100-nmdiameter pores (Figure 9(A)). [74] In a parallel work, the behaviour of osteoblasts and mesenchymal stem cells was studied by Frandsen et al on a series of nanotube sizes, with diameters ranging from 30 to 100 nm. Cell elongation increased as a function of nanotube diameter even above 50 nm, indicating improved differentiation; on the other hand, cell proliferation and adhesion were maximised on 30-nm-diameter nanotubes (Figure 9(B)).…”
Section: Cell Response To Nanotopographymentioning
confidence: 99%